Fetal Thymus Volume Estimation by Virtual Organ Computer‐Aided Analysis in Normal Pregnancies. (1st May 2015) - Re, Claudia; Bertucci, Emma; Weissmann-Brenner, Alina; Achiron, Reuven; Mazza, Vincenzo; Gindes, Liat
Abstract : Objectives: The thymus has a pyramidal shape, which is best shown in coronal planes. The aim of this study was to evaluate the potential of virtual organ computer‐aided analysis to estimate fetal thymus volume in normal pregnancies. Methods: Three‐dimensional volume data sets from the axial upper mediastinal section were acquired from 37 normal pregnancies between 12 and 35 weeks' gestation. Thymus volume was calculated by virtual organ computer‐aided analysis by 2 separate examiners. In 12 cases, volumes were also acquired with 4‐dimensional sonography and spatiotemporal image correlation software to assess the variability in thymus size between the systolic and diastolic periods of fetal heart motion. Linear regression analysis was used to assess the relationship between the fetal thymus volume and gestational age. Paired Student t tests were used to evaluate both the level of agreement for interobserver and intraobserver variability and the difference between diastolic and systolic thymus volumes. Results: Identification of the borders of the thymus and calculation of its volume were successful in 28 patients (77.7%). Statistically significant linear growth of the thymus during pregnancy, from 12 to 35 weeks, was found. The growth coefficient for each gestational age was 0.43 (95% confidence interval, 0.355 to 0.504; P < .001). The difference in thymus size between systole and diastole was minor (0.0798 cm 3 ; 95% confidence interval, –0.044 to 0.203 cm 3 ). Interobserver and intraobserver variability was not statistically significant. Conclusions: Although the thymus has a complex shape, it was possible to determine its borders and to calculate its volume by virtual organ computer‐aided analysis in 77.7% of cases. Linear growth during pregnancy was found, and the minor changes during systole and diastole could be explained by condensation of the soft tissue of the thymus secondary to cardiac activity.